Evolving as a digital scholar : teaching and researching in a digital world - Petegem, Wim van; Bosman, J. P.; De Klerk, Miné; Strydom, Sonja C. (Leuven University Press, 2021)
"What does it take to become a digitally agile scholar? This manual explains how academics can comfortably navigate the digital world of today and tomorrow. It foregrounds three key domains of digital agility: getting involved in research, education and (community) service, mobilising (digital) skills on various levels, and acting in multiple roles, both individually and interlinked with others. After an introduction that outlines the foundations of the three-dimensional framework, the chapters focus on different roles and skills associated with evolving as a digital scholar. There is the author, who writes highly specialised texts for expert peers; the storyteller, who crafts accessible narratives to a broader audience in the form of blogs or podcasts; the creator, who uses graphics, audio, and video to motivate audiences to delve deeper into the material; the integrator, who develops and curates multimedia artefacts, disseminating them through channels such as websites, webinars, and open source repositories; and finally the networker, who actively triggers interaction via social media applications and online learning communities. Additionally, the final chapters offer a blueprint for the future digital scholar as a professional learner and as a ⁰́₈change agent⁰́₉ who is open to and actively pursues innovation. Informed by the authors broad and diverse personal experience, 'Evolving as a Digital Scholar' offers insight, inspiration, and practical advice. It equips a broad readership with the skills and the mindset to harness new digital developments and navigate the ever-evolving digital age. It will inspire academic teachers and researchers with different backgrounds and levels of knowledge that wish to enhance their digital academic profile."--Publisher's description.